PENERAPAN PRINSIP TRANSPARANSI DALAM MEWUJUDKAN PELAYANAN PRIMA PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA KENDARI - Darpin Darpin; Astrid Yunita; Ninik Endang Purwati (Universitas Halu Oleo, 2021)
This study aims to determine and analyze the application of the principle of transparency and the implementation of excellent service at the Kendari City Investment and One Stop Integrated Service Office. This study uses a descriptive qualitative approach, data analysis uses interactive model analysis techniques consisting of data collection, data reduction, data presentation and conclusion drawing/verification. The results showed that the application of the principle of transparency at the Kendari City Investment Office and PTSP from the informative (informative) aspect of the agency was good enough in providing convenience to the public to obtain information either directly or indirectly about services in the field of investment and licensing, in terms of openness has been good enough in conveying information to the public openly, and is easily accessible through several channels of information delivery, on the other hand, the agency still needs to be more intense in explaining all service requirements both technical and administrative in a clear and easy to understand manner using the system. and simple language to the public, from the aspect of disclosure, it is still not optimal in informing the public of financial details and annual reports regarding revenue, financial management and assets of the organization. In terms of the implementation of excellent service in terms of the dimensions of service procedures, service costs, completion time, service products, infrastructure, the overall competence of service providers is good, with the Public Service Standards that have been standardized in 2018.